INVALSI data: methodologies and results III Seminar "INVALSI data: a reasearch tool" - Falzetti, Patrizia (INVALSI per la Ricerca, 2020)
Over the years, interest in data has always grown and, aware of their centrality, many institutions, both public and private, share their data to facilitate the work of all those who wish to use them to interpret phenomena. In the education field, the data produced by INVALSI undoubtedly have a leading role, both at a sample and census level. The availability of data on learning achievements and living conditions of students (the so-called "context data"), as well as on the professional and operational conditions of teachers and School Managers, collected through specific questionnaires, is a valuable source of information based on which it is possible not only to plan improvement interventions in the didactic field, but also to undertake stimulating paths of educational research. This volume hosts four research papers, presented within the III Seminar "INVALSI data: a research tool", which took place in Bari from 26 to 28 October 2018. Thanks to the INVALSI data, the authors conducted interesting in depth analysis of various aspects relating to the Italian education system.